A self-assembled nanotube supported by halogen bonding interactions. Issue 5 (3rd January 2019) - Kennedy, Stuart R.; Main, Mawgan U.; Pulham, Colin R.; Ling, Irene; Dalgarno, Scott J.
Abstract : Upper-rim halogenation of a calix[4]arene modulates the packing of self-assembled nanotubes through the formation of complementary halogen bonding interactions. Abstract : Di-propoxycalix[4]arene is known to self assemble into a nanotube in the solid state. The introduction of two bromine atoms at distal positions across the upper-rim of the calixarene framework modulates nanotube packing, a feature supported by complementary halogen bonding interactions.